Assessment of social validity trends in the journal of applied behavior analysis. Issue 1 (2nd January 2019) - Ferguson, Julia L.; Cihon, Joseph H.; Leaf, Justin B.; Van Meter, Sarah M.; McEachin, John; Leaf, Ronald
ABSTRACT: Montrose Wolf provided a definition and outline of the importance of the assessment of social validity as it applies to the field of applied behavior analysis. Since Wolf's seminal paper, researchers have conducted analyses of the social validity trends of the first 31 years (1968-1998) of the Journal of Applied Behavior Analysis (JABA). The purpose of the current review is to extend the findings those analyses by assessing the trends of the assessment of social validity in JABA from 1999-2016. Overall, the results of the present review indicated that social validity measures were reported in an average of 12% of articles published within JABA that met the inclusion criteria. The results are discussed within the context of the potential implications for the field of applied behavior analysis as well as areas of future research to improve the reporting of the assessment of social validity.